Survey and Excavation at the Henges of the Wharfe Valley, North Yorkshire, 2013 – 15. Issue 1 (2nd January 2018) - Gibson, Alex
Abstract : Large scale geophysical survey has identified two classic henges in the Wharfe Valley and excavation at the henge at Yarnbury has proved its Bronze Age date, reuniting it with antiquarian finds hitherto lacking secure provenance. These henges are placed in their archaeological context suggesting that Wharfedale may have been an important route in cross-Pennine contacts during the third and second millennia BC and that the Neolithic archaeology of this upland region may be more mainstream than peripheral.